(untitled) (International Journal of Engineering and Computer Science, 2014)
Data security is an important issue in military devices. This paper presents a secured and efficient way of sending data and image in encrypted form using Identity Based Cryptography and Visual Cryptography. This has direct application in MANETs specifically for military surveillance [16]. This paper also presents an advantage of using public - private key pairs in Visual Cryptography wherein generally only the private key generators are used. In this paper, the simplicity of RSA algorithm is adopted to set up the public - private key pairs of all the mobile nodes and hence for encryption and decryption [22]. Regeneration of public-private keys is adopted to make the system more secure from various attacks [6].